2014
DOI: 10.1155/2014/289401
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Incorporated Dental Copolymer: Bacterial Growth Inhibition, Mechanical Properties, and Compound Release Rates and Stability by1H NMR

Abstract: Objective. To evaluate bacterial growth inhibition, mechanical properties, and compound release rate and stability of copolymers incorporated with anthocyanin (ACY; Vaccinium macrocarpon). Methods. Resin samples were prepared (Bis-GMA/TEGDMA at 70/30 mol%) and incorporated with 2 w/w% of either ACY or chlorhexidine (CHX), except for the control group. Samples were individually immersed in a bacterial culture (Streptococcus mutans) for 24 h. Cell viability (n = 3) was assessed by counting the number of colony f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other additives to composites and GICs found to be effective against cariogenic bacteria include cetylpyridium chloride, cetrimide [148,150,155,156], benzalkonium chloride [95,146], sodium fusidate [157], 2,2 -bipyridine [158], chitosan [159,160], triclosan [66,149,[161][162][163], propolis [164,165], anthocyanin [166], tetrapod-like zinc oxide whisker (T-ZnOw) [167] and epigallocatechin-2-gallate (EGCG) [11,168,169]. In contrast to most of the other additives, addition of T-ZnOw epigallocatechin-2-gallate resulted in improved mechanical properties [11,167].…”
Section: Other Additivesmentioning
confidence: 99%
“…Other additives to composites and GICs found to be effective against cariogenic bacteria include cetylpyridium chloride, cetrimide [148,150,155,156], benzalkonium chloride [95,146], sodium fusidate [157], 2,2 -bipyridine [158], chitosan [159,160], triclosan [66,149,[161][162][163], propolis [164,165], anthocyanin [166], tetrapod-like zinc oxide whisker (T-ZnOw) [167] and epigallocatechin-2-gallate (EGCG) [11,168,169]. In contrast to most of the other additives, addition of T-ZnOw epigallocatechin-2-gallate resulted in improved mechanical properties [11,167].…”
Section: Other Additivesmentioning
confidence: 99%
“…In addition, recent studies demonstrated that anthocyanins have positive effects on oral health. Anthocyanins showed the protective effect on alveolar bone healing, cytoprotective and anti-inflammatory activity on periodontal tissues, as well as antimicrobial activity against oral pathogens, including Streptococcus mutants and Fusobacterium nucleatum (Desjardins et al 2012; Al-Obaidi et al 2014; Hrynash et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Flexural strength (FS) and Modulus of elasticity (MoE) were calculated using the following formulas 13 :…”
Section: Methodsmentioning
confidence: 99%